Growth response of direct-seeded rice to oxadiazon and bispyribac-sodium in in aerobic and saturated soils - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2011)
Studies were conducted to determine the growth responses of rice to PRE application of oxadiazon and POST application of bispyribac-sodium. Oxadiazon at 1.0 and 1.5 kg ha−1and bispyribac-sodium at 0.030 and 0.045 kg ha−1were applied to four rice varieties (‘IR64’, ‘IR72’, ‘RC09’, and ‘RC18’), which were grown in saturated and aerobic (30% of saturation) soils. Control treatments, where no herbicides were applied, were also included in the study. Shoot and root biomass, and height of rice plants were measured 14 d after application. Phytotoxic effects for both herbicides, including reduced shoot and root biomass, were consistent in all varieties. Rice phytotoxicity symptoms were greater when herbicides were applied to saturated than to aerobic soils. Oxadiazon at 1.0 kg ha−1reduced rice shoot biomass by 22 to 36% in aerobic condition, and 43 to 56% in saturated condition when compared with the control. Bispyribac-sodium reduced rice shoot biomass by 9 to 17% at 0.030 kg ha−1in aerobic soil and 23 to 37% in saturated soil. The results of this study suggest that soil water content is an important factor influencing herbicide phytotoxicity in rice, and its influence warrants further research to improve understanding of physiology of phytotoxicity to minimize the effects of these herbicides on crop production.